Distributed fiber optics 3D shape sensing by means of high scattering NP-doped fibers simultaneous spatial multiplexing - Beisenova, Aidana; Issatayeva, Aizhan; Iordachita, Iulian; Blanc, Wilfried; Molardi, Carlo; Tosi, Daniele (OSA Publishing, 2019)
A novel approach for fiber optics 3D shape sensing, applicable to mini-invasive bio-medical devices, is presented. The approach exploits the optical backscatter reflectometry (OBR) and an innovative setup that permits the simultaneous spatial multiplexing of an optical fibers parallel. The result is achieved by means of a custom-made enhanced backscattering fiber whose core is doped with MgO-based nanoparticles (NP). This special NP-doped fiber presents a backscattering-level more than 40 dB higher with respect to a standard SMF-28. The fibers parallel is built to avoid overlap between NP-doped fibers belonging to different branches of the parallel, so that the OBR can distinguish the more intense backscattered signal coming from the NP-doped fiber. The system is tested by fixing, with epoxy glue, 4 NP-doped fibers along the length of an epidural needle. Each couple of opposite fibers senses the strain on a perpendicular direction. The needle is inserted in a custom-made phantom that simulates the spine anatomy. The 3D shape sensing is obtained by converting the measured strain in bending and shape deformation.
https://www.osapublishing.org/oe/abstract.cfm?uri=oe-27-16-22074
Keywords: 3D shape sensing; optical backscatter reflectometry; OBR; nanoparticles; NP